An EMF cell with a nitrogen solid electrolyte-on the transference of nitrogen ions in yttria-stabilized zirconia - Lee, Doh-Kwon; Fischer, Claus C.; Valov, Ilia; Reinacher, Jochen; Stork, Alexandra; Lerch, Martin; Janek, Jürgen; Justus Liebig University Giessen (My University, 2011)
The mobility and electrochemical activity of nitrogen inside and/or at the surface of ionic compounds is of fundamental, as well as of possibly practical, relevance. In order to better understand the role of nitrogen anions in solid electrolytes, we measured the transference number of nitrogen in yttria-stabilized zirconia (YSZ) by a concentration cell technique as a function of oxygen activity at different temperatures in the range of 1023 <= T/K <= 1123. YSZ doped with 1.9 wt% of N (YSZ: N) turned out to have an appreciable nitrogen transference number, which increased from 0 to 0.1 with decreasing oxygen activity in the range of -20 < loga(O2) < -14. The stability of N in YSZ: N, however, has yet to be elucidated under oxidizing conditions.
Keywords: nitrogen; mobility; electrochemical activity; transference number; yttria stabilized zirconia (YSZ); ddc:540